The Effect of Barrier Hops and Jump-to-Box Practices on Shooting Ability in Students at Persegrata Palembang Football School (SSB) - Saputra, Ade Indra (Journal of Social Work and Science Education, 2023)
This research is an experiment with the pretest-posttest control group design method. The type of research used in this study is a type of experimental research with a quasi-experimental design. This research is experimental research and the research design used is a Quasi-Experimental Design, namely the Group Pretest Posttest Design. The sample used in this study were players aged 13-15 years, Persegrata Palembang football school (SSB) students in 2023, totaling 10 players. The sampling technique in this study used a systematic sampling technique and an ordinal pair system. This research as a whole used test, measurement, and documentation methods. The results of the study showed differences between the group of students who used the barrier hop training model and those who used the jump-to-box training model for their shooting abilities. This means that the training model has a significant role in shooting ability. Also, there are differences in passing and shooting skills between groups of students who receive the barrier hop training model and the group of students who receive the jump-to-box training model.